Ethylene receptors and related proteins in climacteric and non-climacteric fruits. (November 2018) - Chen, Yi; Grimplet, Jérôme; David, Karine; Castellarin, Simone Diego; Terol, Javier; Wong, Darren C.J.; Luo, Zhiwei; Schaffer, Robert; Celton, Jean-Marc; Talon, Manuel; Gambetta, Gregory Alan; Chervin, Christian
Highlights: Ethylene perception proteins in climacteric or non-climacteric fruits are compared. Climacteric fruits have a higher number of ethylene receptor (ETR) genes. A higher number of receptors may require more ethylene gas to initiate ripening. Non-climacteric fruits may have an earlier ETR peak relative to sugar accumulation. This is a foundation for the annotation of ethylene perception genes in fruits. Abstract: Fruits have been traditionally classified into two categories based on their capacity to produce and respond to ethylene during ripening. Fruits whose ripening is associated to a peak of ethylene production and a respiration burst are referred to as climacteric, while those that are not are referred to as non-climacteric. However, an increasing body of literature supports an important role for ethylene in the ripening of both climacteric and non-climacteric fruits. Genome and transcriptomic data have become available across a variety of fruits and we leverage these data to compare the structure and transcriptional regulation of the ethylene receptors and related proteins. Through the analysis of four economically important fruits, two climacteric (tomato and apple), and two non-climacteric (grape and citrus), this review compares the structure and transcriptional regulation of the ethylene receptors and related proteins in both types of fruit, establishing a basis for the annotation of ethylene-related genes. This analysis reveals two interesting differences between climacteric and non-climacteric fruit: i) a higher number of ETR genes are found in climacteric fruits, and ii) non-climacteric fruits are characterized by an earlier ETR expression peak relative to sugar accumulation.